The Use of Quality Pedagogic Language in the Teaching of English in Indonesian Setting - Suherdi, Didi (EDUCARE, 2012)
ABSTRACT: The implementation of new curriculum into the teaching of English in Indonesia requires new ways of doing classroom practices. This article is intended to prtesent the result of a research conducted by a team of researchers (Suherdi, Yusuf & Muslim, 2007) in an SMA (Sekolah Menengah Atas or Senior High School) in Bandung, West Java, Indonesia to ascertain the effectiveness of the use of quality pedagogic language in improving studentsâ achievement in English. For that purpose, an experiment has bee done in a first grade class. Using a quasi-experimental design, the class has been taught using the language thus far used by the teacher in the first six meetings, and using the quality pedagogic language in the following six meetings. Prior to the first meetings, a pre-test was conducted to ascertain studentsâ learning achivement before the treatment. Then, a post-test was conducted at the end of the experiment. The result of the data analysis showed that there was a significant difference between the pre-test and post-test means in the English competence, and no difference in those of their effective factors. Possible explanations to these unlinear patterns of findings have been presented and relevant recommendations have been given both for theoretical and practical aspects of English teaching, especially in schooling system.KEY WORDS: Pedagogic language, teachersâ questions, feedback, pauses, discourse analysis, affective factors, and teaching of English.About the Author: Prof. Dr. H. Didi Suherdi is a Senior Lecturer at the Department of English Education, Faculty of Language and Art Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. He can be reached at: suherdi_d@yahoo.comHow to cite this article? Suherdi, Didi. (2012). âThe Use of Quality Pedagogic Language in the Teaching of English in Indonesian Settingâ in EDUCARE: International Journal for Educational Studies, Vol.4(2) February, pp.111-124. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 12, 2011); Revised (January 23, 2012); and Published (February 17, 2012).